Specific interaction of cellular factors with the B enhancer of polyoma virus. - Piette, J (1985)
Specific interactions between proteins from mouse 3T6 cells and the enhancer sequence of polyoma virus were detected using the method of band shifting on polyacrylamide gels. Proteins eluted from 3T6 nuclei using a buffer containing 0.55 M NaCl, formed a stable complex with the B enhancer of polyoma virus. At least two different factors are involved in this interaction. The contact sites which were mapped on the DNA sequence using DNase I footprinting correspond to a GC-rich palindrome surrounded by two sequences homologous respectively to the immunoglobulin and to the immunoglobulin and SV40 enhancers. Moreover Bal31 deletion analysis confirmed that similar sequences are required for the formation of the complex. In spite of a common function and partial sequence homology among some enhancers, neither the polyoma A enhancer, the mouse immunoglobulin heavy chain gene enhancer, nor the origin-promoter-enhancer region of SV40 efficiently competed with the polyoma B enhancer for the binding of these molecules.